Design issues concerning thermofluidynamic and acoustic aspects in a diesel engine suitable for aeronautical applications. (7th May 2009) - Bozza, F.; Costa, M.; Siano, D.
Some aspects concerning the development of a prototype of a supercharged diesel engine suitable for aeronautical applications are discussed. The engine, equipped with a common rail fuel injection system, is conceived in a two-stroke uniflow configuration, aimed at achieving a weight to power ratio equal to 1 kg kW -1 . Computational 1D and 3D analyses are carried out to support the design phase and to address some particular aspects of the engine operation, such as the scavenging process, the engine-turbocharger matching, the fuel injection and the development of combustion. The exchange of information between the two employed codes improves the accuracy of the achieved results. In addition, the computed pressure cycles are used to numerically predict the combustion noise, by means of an integration of the Finite Element Method and the Boundary Element Method. The obtained results are suitable to be used as driving parameters for successive engine structural design.